Review of the curricular design applied to mechatronics in relation to the labor field. (Innovation & Development in Engineering and Applied Science, 2025)
This article presents a review of the curricular design in mechatronics, aligned with the needs of the educational sector and the industrial field. Key components such as the integration of pedagogical knowledge and the development of technical competencies in fundamental areas such as educational robotics, mechanics, programming, design, electricity and electronics are examined, which facilitates the teaching of these disciplines in educational institutions. The research highlights the importance of training professionals capable of educating future generations in technical areas, as well as performing effectively in industrial sectors, strengthening the link between the university and contemporary social and technological demands. The study emphasizes the need to continually update curricular content, integrating essential pedagogical aspects such as didactic planning, formative evaluation and the use of active and collaborative methodologies, together with emerging technologies such as artificial intelligence (AI), advanced manufacturing and virtual simulation. It is emphasized that the flexibility of the curriculum, both pedagogically and technically, is crucial for students to adapt to the educational field of mechatronics and the dynamic industrial environment. This approach ensures effective interaction between the university, society and industry, promoting comprehensive education that not only responds to the needs of the productive sector, but also to the growing demand for educators specialized in technology.
Keywords: Curriculum design; Mechatronics; Labor field; Professional skills